Illocutionary Act Used by The Main Character in Movie Guardians of The Galaxy Vol.2 - Nisa, Baiatun; Mulyani , Cantik Novia; Nurmalia , Lia; Sari , Sulhizah Wulan (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2022)
This study aims to determine the types and most prominent illocutionary acts used by the main character in James Gunn's fantasy movie Guardians of the Galaxy Vol.2. The research conducted a descriptive qualitative using Searle's taxonomy of illocutionary acts theory. There were 42 utterances found. The data analysis was performed by categorizing into representative, directive, commissive expressive, and declarative. The results showed that the most prevalent type of speech act was representative (69%) which included predicting, informing, asserting, rejecting, claiming, thinking, and believing. It was followed by directives (21%) in commanding, advising, and asking. Expressive (%) involved gratitude, apologizing, regretting, and like. Commissive (2%) contained committing the speaker to do something in the future. The dominant illocutionary act used by the main character were representatives. The main character tended to convey his utterance for describing states or events in the world that he believed it to be. Meanwhile, the main character did not use declarative at all since this act requires authority and status to do. Thus, the main character lacked any sort of power or authority in any position in the world to change the world through words.